Symbols of the Sacred Religious Tension in Act 1, Scene 1 of Romeo and Juliet - Ward, Angela (2017)
Etymology and religious context reveal a culturally, historically accurate interpretation of Act I, scene I of William Shakespeare's Romeo and Juliet. This analysis presents allusions to the Geneva Bible, references to Catholic dogma and icons, Protestant imagery, and spectres of governmental censorship, which are woven throughout the opening scene to reveal a more wide ranging perspective of the plot than the current, reductive and simplistic approach to the scene. An analysis focused on the heightened religious tension between the Capulet and Montague households is relevant for audiences as they decontextualize and construct the play for themselves, as Elizabethans did.
Keywords: Bibel